Intra-industry trade, involuntary unemployment and macroeconomic stability - Le Riche, Antoine,Lloyd-Braga, Teresa,Modesto, Leonor (IZA - Institute of Labor Economics, 2021)
We study the impact of intra-industry trade and capital mobility on steady state welfare and on the stability properties of two countries with identical technologies and preferences. We consider a two-factor overlapping generations model, featuring one-sector of differentiated goods with taste for variety. There is imperfect competition in the output market and increasing returns to scale in production (fixed costs and externalities). In one country there is full employment and saddle path stability in autarky, whereas in the other there are efficiency wages, and the autarkic equilibrium may be locally indeterminate. After opening the borders, the rigid wage country may export indeterminacy to the full employment country, particularly if it is big enough. In contrast, when the full employment country is sufficiently big, local indeterminacy, and therefore expectations driven fluctuations may be eliminated in the world. In any case, stochastic and deterministic fluctuations (associated with local indeterminacy and bifurcations) are possible with smaller externalities, whatever the relative size of the two countries. Steady state welfare improves in the full employment country with free trade and capital mobility, while unemployment increases in the country with labor market rigidities, reducing welfare. We also find that taste for variety (and therefore intra-industry trade), reduces the likelihood of local indeterminacy, but leads to flip bifurcations under more plausible values of the model parameters.
10419/232799
Keywords: Graue Literatur; bifurcations; indeterminacy; intra-industry trade; taste for variety; involuntary unemployment